Sustainable Practices Amid the Covid-19 Pandemic of A Construction Company in Cebu, Philippines - Neri, Rico Serafin B.; Polinar, Mark Anthony N. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
The construction industry in Cebu City is growing, but sustainability is essential, especially during times of crisis like the COVID-19 pandemic. Some businesses have not enhanced their sustainable practices to survive the new normal. The main objective of this study is to explore the triple bottom line of a construction company in Cebu City, Philippines. The study employed a descriptive-correlational research design, and the sample comprised 58 rank-and-file employees selected through a simple random sampling method. The collected data were analyzed, tabulated, and interpreted using various statistical techniques, namely weighted mean, and Pearson correlation coefficient. The study found that the organization placed a high level of importance on social and economic sustainability, while environmental sustainability was considered moderately significant. The relationship between these three variables was examined, and it was determined that they were positively correlated. The study's conclusion emphasized that balancing economic growth, social inclusion, and environmental preservation is crucial for long-term sustainability. Therefore, prioritizing these aspects can improve a company's performance and contribute to its long-term sustainability.